2013
DOI: 10.1093/eurjhf/hft111
|View full text |Cite
|
Sign up to set email alerts
|

Dabigatran compared with warfarin in patients with atrial fibrillation and symptomatic heart failure: a subgroup analysis of the RE‐LY trial

Abstract: AimsWe evaluated the effects of dabigatran compared with warfarin in the subgroup of patients with previous symptomatic heart failure (HF) in the RE-LY trial. Methods and resultsRE-LY compared two fixed and blinded doses of dabigatran (110 and 150 mg twice daily) with open-label warfarin in 18 113 patients with AF at increased risk for stroke. Among 4904 patients with HF, annual rates of stroke or systemic embolism (SE) were 1.92% for patients on warfarin compared with 1.90% for dabigatran 110 mg [hazard ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
2
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 36 publications
8
82
2
9
Order By: Relevance
“…Длительная антикоагу-лянтная терапия пока остается единственной доказан-ной возможностью влияния на прогноз в данной по-пуляции больных [16][17][18][19]. Результаты популяционных исследований показывают низкую распространенность длительной антикоагулянтной терапии.…”
Section: Discussionunclassified
“…Длительная антикоагу-лянтная терапия пока остается единственной доказан-ной возможностью влияния на прогноз в данной по-пуляции больных [16][17][18][19]. Результаты популяционных исследований показывают низкую распространенность длительной антикоагулянтной терапии.…”
Section: Discussionunclassified
“…The presence of AFib on the baseline ECG did not increase the significant risk of stroke associated with a history of AFib. To the best of our knowledge this is the first report to 2,7,[12][13][14][15] this analysis indicates that a history of AFib is also associated with an increased risk of cardiovascular morbidity and mortality, including stroke. These results, therefore, suggest that a history of AFib should be taken into consideration when assessing the risks of AFib in patients with HFpEF regardless of whether AFib is present on ECG.…”
Section: Discussionmentioning
confidence: 65%
“…2,7,[12][13][14]16 Studies have compared the risk of stroke in patients with AFib and HFrEF or HFpEF. A subgroup analysis of the AFib Follow up Investigation of Rhythm Management (AFFIRM) trial found that although the history of stroke was more prevalent in patients with HFpEF compared with HFrEF at baseline (16% versus 11%), the subsequent incidence of stroke during the study was no different between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…20 The Randomized Evaluation of LongTerm Anticoagulant Therapy trial of dabigatran included 4904 patients with symptomatic heart failure. 21 Although patients with heart failure had higher mean CHADS 2 scores, there was no significant interaction between the 2 tested dabigatran doses and the presence of symptomatic heart failure in relation to the primary outcome. Importantly, the NOACs showed similar risk of major bleeding in patients with or without heart failure.…”
Section: Circulationmentioning
confidence: 81%